2019
DOI: 10.1126/scitranslmed.aav3879
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid suppression of cathelicidin drives dysbiosis and bacterial infection in chronic obstructive pulmonary disease

Abstract: Bacterial infection commonly complicates inflammatory airway diseases such as chronic obstructive pulmonary disease (COPD). The mechanisms of increased infection susceptibility and how use of the commonly prescribed therapy inhaled corticosteroids (ICS) accentuates pneumonia risk in COPD are poorly understood. Here, using analysis of samples from patients with COPD, we show that ICS use is associated with lung microbiota disruption leading to proliferation of streptococcal genera, an effect that could be recap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 91 publications
0
65
0
1
Order By: Relevance
“…Existing data indicate that ACE2 is expressed primarily in the nasal and bronchial epithelium and is absent from immune cells (16). Given our prior data indicating that FP also exerts its inhibitory effects on immunity principally at the pulmonary epithelium (8,23), we next assessed whether suppressive effects on ACE2 were also observed following ex vivo ICS administration in cultured COPD bronchial epithelial cells (BECs, Fig 5a). Baseline characteristics of the subjects included in these analyses are shown in table 2.…”
Section: The Suppressive Effect Of Ics Upon Ace2 Expression Occurs Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data indicate that ACE2 is expressed primarily in the nasal and bronchial epithelium and is absent from immune cells (16). Given our prior data indicating that FP also exerts its inhibitory effects on immunity principally at the pulmonary epithelium (8,23), we next assessed whether suppressive effects on ACE2 were also observed following ex vivo ICS administration in cultured COPD bronchial epithelial cells (BECs, Fig 5a). Baseline characteristics of the subjects included in these analyses are shown in table 2.…”
Section: The Suppressive Effect Of Ics Upon Ace2 Expression Occurs Atmentioning
confidence: 99%
“…Primary cells were cultured in collagen coated T75 flasks in LH-9 medium until 80% confluent before being seeded at 2.5 x 10 5 cells per well in a 24-well plate. Cells were treated with 10nM FP (Sigma-Aldrich) or vehicle dimethyl sulfoxide (DMSO), as previously reported (23).…”
Section: Treatment Of Cultured Primary Bronchial Epithelial Cellsmentioning
confidence: 99%
“…Murray et al (2006) has underlined the synergistic effect of viral infection with other sensitizing agents in causing more severe acute exacerbations in the airway. This is especially true when not all exacerbation events occurred during the viral infection but may also occur well after viral clearance (Kim et al, 2008;Stolz et al, 2019) in particular the late onset of a bacterial infection (Singanayagam et al, 2018(Singanayagam et al, , 2019a. In addition, viruses do not need to directly infect the lower airway to cause an acute exacerbation, as the nasal epithelium remains the primary site of most infections.…”
Section: Novel Mechanisms In the Upper Airway Hypothesized To Contribmentioning
confidence: 99%
“…Moreover, a viral infection may also alter the nutrient profile in the airway through release of previously inaccessible nutrients that will alter bacterial growth (Siegel et al, 2014;Mallia et al, 2018). Furthermore, the destabilization is further compounded by impaired bacterial immune response, either from direct viral influences, or use of corticosteroids to suppress the exacerbation symptoms (Singanayagam et al, 2018(Singanayagam et al, , 2019aWang et al, 2018;Finney et al, 2019). All these may gradually lead to more far reaching effect when normal flora is replaced with opportunistic pathogens, altering the inflammatory profiles (Teo et al, 2018).…”
Section: Alteration Of Airway Microbiomementioning
confidence: 99%
“…Existing evidence supports the former of these 2 mechanisms as evaluation of the in vivo effects of ICSs in animal models and patients with COPD has indicated disruption of the endogenous microbiota with increased relative abundance of the genus Streptococcus. 8 Using mouse models to understand cause and effect, we identified that impairment of lung bacterial control by ICSs occurs mechanistically through suppression of epithelial production of the antimicrobial peptide cathelicidin. 8 In contrast to wild-type mice, FP had no effect on bacterial loads in Streptococcus pneumoniae-infected cathelicidin-deficient (Camp 2/2 ) mice, whereas recombinant cathelicidin protein could reverse FP-mediated increases in Streptococci within the microbiota, indicating that cathelicidin is necessary and sufficient for FP to impart its adverse effects on host defense.…”
mentioning
confidence: 99%